Finite Complement Clauses in Disciplinary Research Articles Authored by Filipino Academic Writers - Punla Hernandez, Hjalmar (rEFLections, 2024)
Finite complement clauses (FCCs) are an understudied syntactic structure of L2 advanced academic writing. The present study cross-investigated FCCs in qualitative (QUALI) and quantitative (QUANTI) research articles written by Filipino academic writers (FAWs) in Applied Linguistics (APPLING), Communication (COMM), and Measurement and Evaluation (MEEV). Specifically, it determined the FCCs with the most occurrences across five disciplinary research article sub-registers and identified whether these FCCs differ significantly in terms of frequencies of use. With Hernandez’s (2021) framework adapted from Biber and Gray’s (2016) study, this research analyzed five FCCs in 42 disciplinary research articles. Major results revealed that verb-controlled that-clauses (with 33.69 as normalized frequency count) outnumbered other FCCs in research article sub-registers across disciplines. They were more recurrent in QUALI and QUANTI APPLING research articles (7.91 and 7.54, respectively) and QUANTI and QUALI COMM research articles (7.34 and 6.96, respectively) than in QUANTI MEEV research articles (3.94). In addition, a significant difference exists between them and other FCCs at the p<.05 level in terms of frequencies of use. In view of these findings, it can be concluded that verb-controlled that-clauses are the most useful FCCs in APPLING, COMM, and MEEV research articles. Likewise, FAWs across the three disciplines write more informally as signposted by their repeated use of that complementizer with these FCCs controlled by verbs. The study draws its implications for academic writing instruction.